Cultural differences in professional communication: academic and business contexts. - Mokhniuk, Anna (Economic Journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. Globalization has made effective professional communication essential for economists in both academic and business contexts. Cultural differences influence academic writing, business interactions, and negotiation styles, requiring adaptation to diverse communication norms. Purpose of the Article. The main objective of the article is to analyse the impact of cultural differences on professional communication in economics, focusing on both academic and business contexts. Methods. A qualitative, comparative, and interdisciplinary approach is applied, integrating Hofstede’s Cultural Dimensions Theory and Erin Meyer’s Culture Map. The research integrates theoretical analysis, comparative country studies, and case-based insights to explore how economists navigate academic and business communication across diverse cultural settings. Results. The study finds that cultural differences significantly affect academic writing, negotiation styles, feedback mechanisms, and leadership approaches. The results reveal that Ukraine’s hierarchical and collectivist culture fosters formal and authority-driven communication, whereas the USA’s individualistic and low-context culture emphasizes directness and efficiency. Japan’s high-context communication relies on indirect messaging and consensus-building, while Sweden’s egalitarian approach promotes open dialogue and participatory decision-making. These differences present challenges for economists navigating academic publishing, international collaborations, and global business interactions. Conclusions. Cultural intelligence, collaborative engagement, and strategic adaptation are essential for economists to succeed in cross-cultural academic and business environments. Economists must balance local and global expectations and adapt their communication strategies. Future research should explore the role of AI-driven language tools, digital platforms, and effective strategies in shaping professional communication in economics.
Keywords: professional communication; intercultural differences; professional communication; academic communication; business communication; intercultural competence; digitalization; 316.74:378.4:339.13